Evaluation of the Effects on Regional Production and Employment in Spain of the Renewable Energy Plan 2011–2020 - Blanco, Miguel (2021)
The Renewable Energy Plan for the period 2011–2020 established as a general goal to ensure that renewable sources represent at least 20% of final energy consumption in 2020, together with a minimum contribution of 10% from renewable energy sources in transportation for that year. Then, the goal of this research is to evaluate the effects of the regional production of clean energy, identifying the employment generated in the renewable sector. The adopted methodology was the shift-share analysis, frequently used by researchers to analyze territorial differences. Main results showed important differences, at regional level, in the production of this type of energy. Likewise, we used constant shift and constant share methodology to make a forecast on the evolution of the sector from the data of last published years. Pending the approval of the new Renewable Energy Plan for the period 2021–2030, the results obtained in this research allow the identification of the regions that showed a favorable evolution to the energy change and identifies the projects that generate employment and production in the sector.